Risk of Major Congenital Malformations and Exposure to Antiseizure Medication Monotherapy. - Battino D; Tomson T; Bonizzoni E; Craig J; Perucca E; Sabers A; Thomas S; Alvestad S; Perucca P; Vajda F; EURAP Collaborators; Kiteva Trenchevska, Gordana (American Medical Association, 2024)
Importance: Women with epilepsy (WWE) require treatment with antiseizure medications (ASMs) during pregnancy, which may be associated with an increased risk of major congenital malformations (MCMs) in their offspring. Objective: To investigate the prevalence of MCMs after prenatal exposure to 8 commonly used ASM monotherapies and changes in MCM prevalence over time. Design, setting, and participants: This was a prospective, observational, longitudinal cohort study conducted from June 1999 to October 2022. Since 1999, physicians from more than 40 countries enrolled ASM-treated WWE before pregnancy outcome was known and followed up their offspring until 1 year after birth. Participants aged 14 to 55 years who were exposed to 8 of the most frequently used ASMs during pregnancy were included in this study. Data were analyzed from April to September 2023. Exposure: Maternal use of ASMs at conception. Main outcomes and measures: MCMs were assessed 1 year after birth by a committee blinded to type of exposure. Teratogenic outcomes across exposures were compared by random-effects logistic regression adjusting for potential confounders and prognostic factors. Results: A total of 10 121 prospective pregnancies exposed to ASM monotherapy met eligibility criteria. Of those, 9840 were exposed to the 8 most frequently used ASMs. The 9840 pregnancies occurred in 8483 women (mean [range] age, 30.1 [14.1-55.2] years). MCMs occurred in 153 of 1549 pregnancies for valproate (9.9%; 95% CI, 8.5%-11.5%), 9 of 142 for phenytoin (6.3%; 95% CI, 3.4%-11.6%), 21 of 338 for phenobarbital (6.2%; 95% CI, 4.1%-9.3%), 121 of 2255 for carbamazepine (5.4%; 95% CI, 4.5%-6.4%), 10 of 204 for topiramate (4.9%; 95% CI, 2.7%-8.8%), 110 of 3584 for lamotrigine (3.1%; 95% CI, 2.5%-3.7%), 13 of 443 for oxcarbazepine (2.9%; 95% CI, 1.7%-5.0%), and 33 of 1325 for levetiracetam (2.5%; 95% CI, 1.8%-3.5%). For valproate, phenobarbital, and carbamazepine, there was a significant increase in the prevalence of MCMs associated with increasing dose of the ASM. Overall prevalence of MCMs decreased from 6.1% (153 of 2505) during the period 1998 to 2004 to 3.7% (76 of 2054) during the period 2015 to 2022. This decrease over time was significant in univariable logistic analysis but not after adjustment for changes in ASM exposure pattern. Conclusions and relevance: Of all ASMs with meaningful data, the lowest prevalence of MCMs was observed in offspring exposed to levetiracetam, oxcarbazepine, and lamotrigine. Prevalence of MCMs was higher with phenytoin, valproate, carbamazepine, and phenobarbital, and dose dependent for the latter 3 ASMs. The shift in exposure pattern over time with a declining exposure to valproate and carbamazepine and greater use of lamotrigine and levetiracetam was associated with a 39% decline in prevalence of MCMs, a finding that has major public health implications.